2001
DOI: 10.1021/ja011540e
|View full text |Cite
|
Sign up to set email alerts
|

Ru3(CO)12-Catalyzed Coupling Reaction of sp3C−H Bonds Adjacent to a Nitrogen Atom in Alkylamines with Alkenes

Abstract: Catalytic reactions which involve the cleavage of an sp(3) C-H bond adjacent to a nitrogen atom in N-2-pyridynyl alkylamines are described. The use of Ru(3)(CO)(12) as the catalyst results in the addition of the sp(3) C-H bond across the alkene bond to give the coupling products. A variety of alkenes, including terminal, internal, and cyclic alkenes, can be used for the coupling reaction. The presence of directing groups, such as pyridine, pyrimidine, and an oxazoline ring, on the nitrogen of the amine is crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
128
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(149 citation statements)
references
References 63 publications
7
128
0
6
Order By: Relevance
“…The syntheses of these compounds have attracted much attention in industrial and academic research because of their biological and pharmaceutical properties. Recently, some excellent examples based on the direct sp 3 C-H bond activation adjacent to a nitrogen atom for C-C bond formations were reported by Murahashi et al (7), Murai and coworkers (8)(9)(10)(11), Ishii and coworkers (12), Sames and coworkers (13)(14)(15), Davies et al (16,17), Yoshimitsu et al (18), Yoshida and coworkers (19)(20)(21)(22), and Yi and coworkers (23). Although these are elegant methodologies, most of them required another functionalized substrate.…”
mentioning
confidence: 99%
“…The syntheses of these compounds have attracted much attention in industrial and academic research because of their biological and pharmaceutical properties. Recently, some excellent examples based on the direct sp 3 C-H bond activation adjacent to a nitrogen atom for C-C bond formations were reported by Murahashi et al (7), Murai and coworkers (8)(9)(10)(11), Ishii and coworkers (12), Sames and coworkers (13)(14)(15), Davies et al (16,17), Yoshimitsu et al (18), Yoshida and coworkers (19)(20)(21)(22), and Yi and coworkers (23). Although these are elegant methodologies, most of them required another functionalized substrate.…”
mentioning
confidence: 99%
“…[92][93][94] Indeed, with the exception of the present authors work, [95][96][97][98][99] all other late transition metal catalyzed hydroaminoalkylations require pyridyl directing groups in combination with mono-olefin reactants. [100][101][102][103][104][105][106][107][108] In a significant departure from prior art, it was found that ruthenium catalyzed hydrogen transfer from 4-aminobutanol to 1-substituted-1,3-dienes results in the generation of dihydropyrrole-allylruthenium pairs, which combine to form products of hydroaminoalkylation with good to complete control of anti-diastereoselectivity (Scheme 18). 95 As corroborated by deuterium labeling experiments, kinetically preferred hydrometalation of the terminal olefin of the 1-substituted-1,3-diene delivers a 1,1-disubstituted π-allylruthenium complex that isomerizes to the more stable monosubstituted π-allylruthenium complex.…”
Section: Hydroaminoalkylationmentioning
confidence: 99%
“…Path B would result in the formation of an iminium intermediate, which in turn would react with H 2 O as nucleophile. In path A, 18 O incorporation could occur if the putative iron-oxo intermediate attacking the C α -H bond is formed through reaction with H 2 O or if exchange between the oxo ligand and external H 2 O is possible. As such pathways have been documented in previous studies, 17 both pathways A and B are possible for the discussed amine oxidation.…”
Section: Scheme 12 Incorporation Of 18 O Into Amide Productmentioning
confidence: 99%
“…Indeed, several methodologies in the literature are known that realize such amine C α -H functionalizations to form new C α -alkyl, 18,19 C α -alkynyl, 20 C α -Ar, 21 C α -Ac, 22 and C α -CN 23 bonds.…”
Section: Scheme 13 Mechanistic Hypotheses For Iron-catalyzed C α -H Omentioning
confidence: 99%